A Study on the correlation between the levels of self-esteem and uncertainty in initial interaction of freshman students from the University of the Philippines Diliman - Sanchez, Karmia P. (College of Arts and Letters, University of the Philippines Diliman, 2019)
Transition into college has implicated different adjustments and challenges that freshman students must face, such as academic adjustment, emotional, and social adjustment. Social adjustment is one of the most fundamental adjustments that adolescents have to engage with, and it requires students to have a positive self-esteem in order for them to adjust well in college. Moreover, freshman students, as they step inside the university, will have to face new people and begin build a new relationship with them. When individuals encounter new people for the first time, they experience and with a lot of uncertainties that they wish to reduce if they want to pursue a closer relationship with the other person. This study focused on the correlation between the levels of self-esteem and uncertainty in initial interaction of freshman students from the University of the Philippines Diliman. The specific research objectives were 1)to determine the level of self-esteem of the freshman students from the University of the Philippines Diliman; 2)to determine the level of uncertainty in initial interaction of the freshman students from the University of the Philippines Diliman; 3)to determine the correlation between the level of self-esteem and level of uncertainty in initial interaction of the freshman students from the University of the Philippines Diliman. The theoretical framework of the study was comprised of the Uncertainty Reduction Theory by Charles Berger (1975) and the concept of Self-Esteem as defined by Rosenberg (1965). The respondents of the study were freshman students from six (6) Speech 30 classes in the University of the Philippines Diliman. Purposive random sampling was employed. The researcher used a survey in order to gather the data needed for the study, which is composed of the Rosenberg's (1965) Self-Esteem Scale and Clatterbuck's (1979) CLUES 7. A total of 92 valid survey response forms were collected and analyzed. Based on data gathered and analyzed, the need to improve freshman students' level of self-esteem as they have a generally low level of self-esteem, which affects their academic and social performance, is necessary for the students to adjust well in their first year in college. The students may perceive themselves negatively and have a low self-worth. It was also found in the study that the students have above average level of uncertainty in initial interaction which may affect their future relationship with their classmates. Results also showed that the freshman students from the University of the Philippines Diliman have a stong inverse relationship between their level of self-esteem and level of uncertainty in initial interaction; as students' level of self-esteem goes up, their level of uncertainty in initial interaction lessens. The inverse relationship between the levels of self-esteem and uncertainty indicates that students may find it difficult to interact with another, especially during initial interaction with their fellow classmates, as they generally have a high level of uncertainty.